(3,8*1.75/10+1,02)+0,4*2,6*2,6-0,1*0,1*0,1
Calculat in ordine
Răspunsuri la întrebare
Răspuns de
2
(3,8·1,75/10+1,02)+0,4·2,6·2,6-0,1·0,1·0,1=
=(6,65/10+1,02)+0,4·2,6·2,6-0,1·0,1·0,1=
=(0,665+1,02)+0,4·2,6·2,6-0,1·0,1·0,1=
=1,685+0,4·2,6·2,6-0,1·0,1·0,1=
=1,685+2.704-0,001=
=4.389-0,001=
=4.388
=(6,65/10+1,02)+0,4·2,6·2,6-0,1·0,1·0,1=
=(0,665+1,02)+0,4·2,6·2,6-0,1·0,1·0,1=
=1,685+0,4·2,6·2,6-0,1·0,1·0,1=
=1,685+2.704-0,001=
=4.389-0,001=
=4.388
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă